2015
DOI: 10.1038/srep11803
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an Association between the SDF-1 rs1801157 Polymorphism and Coronary Heart Disease: A Meta-Analysis

Abstract: Recent studies have shown that the single-nucleotide polymorphism (SNP) rs1801157 in the stromal cell-derived factor (SDF)-1 gene is associated with susceptibility to coronary heart disease (CHD). However, published studies have shown inconsistent results. Therefore, a meta-analysis was carried out to evaluate the association between rs1801157 and CHD in the literature. A systematic literature search was performed using the PubMed, Web of Science, Cochrane Library, Chinese National Knowledge Infrastructure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
13
1
Order By: Relevance
“…Moreover, we also found that rs1801157 was not reported by other GWASs concerning hematological malignancy after searching all known GWAS databases, such as GWAS Central. The reason may be that GWAS cannot identify all of the SNPs involved in a single action 39. Up to now, the reports concerning the relationship between SDF1 -3′A polymorphism and the risk of hematological malignancy have all mostly been based on the small-scale case-control studies 20,21,2329.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we also found that rs1801157 was not reported by other GWASs concerning hematological malignancy after searching all known GWAS databases, such as GWAS Central. The reason may be that GWAS cannot identify all of the SNPs involved in a single action 39. Up to now, the reports concerning the relationship between SDF1 -3′A polymorphism and the risk of hematological malignancy have all mostly been based on the small-scale case-control studies 20,21,2329.…”
Section: Discussionmentioning
confidence: 99%
“…The related pooled analysis carried out by Tong et al suggested that SDF-1 rs1801157 polymorphism showed close association with cancer risk among Asians, especially influencing the susceptibility of urologic and lung cancers [ 24 ]. However, Wang et al found that there were no significant association between SDF-1 rs1801157 polymorphism and coronary hear disease based on 7 articles [ 25 ]. The conclusion of Wang et al was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] A meta analysis performed by Wu et al suggested that rs1801157 was significantly associated with a decreased risk of myocardial infarction. [ 38 ] Furthermore, SDF1 rs1801157 has been demonstrated to influence protein expression levels. [ 39 ] There exist controversial data on the influence of the afore mentioned polymorphism on cardiovascular disease, especially when Chinese and Caucasian population are compared.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for selection of variants in these genes were a representative allele frequency in Caucasians and clear evidence for functional consequences based on in vitro/in vivo data. [ 22 , 23 , 24 , 25 , 26 ] Thus, the following polymorphisms of SDF1 were analysed: rs1065297, rs2839693, rs1801157, rs266087, rs266085 and rs266089. Genotyping for SDF1 variants was performed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) using the MassARRAY ® Compact system (Sequenom, CA, USA) as previously described.…”
Section: Methodsmentioning
confidence: 99%